Two new species of Phialiphora (Spermacoceae, Rubiaceae) exemplify drought adaptations in western Madagascar - Petra De Block; Franck Rakotonasolo; Alexander Vrijdaghs; Steven Dessein (Plant Ecology and Evolution, 2020)
Background – Phialiphora (Spermacoceae, Rubiaceae) is a herbaceous genus restricted to unconsolidated white sands in open spaces in dry forests in northwestern Madagascar. The genus is characterized by the semi-succulent nature of its leaves and stems, its basal leaf rosette, its head-like inflorescences subtended by large leaf-like involucrate bracts and its isostylous flowers. Hitherto, only two species were described.Methods – Classical methods of herbarium taxonomy are followed.Key results – Two new Phialiphora species, P. glabrata De Block and P. valida De Block, are described, which brings the number of species in the genus to four. The two new species differ from the two previously described species by their glabrous branches, bracts, ovaries, calyces and fruits. They are easily distinguished from each other by the shape and size of the calyx lobes. A detailed description, illustration, distribution map and preliminary conservation assessment is given for the new species, which are assessed as critically endangered. We also present a key for the genus and discuss in detail the typical branching system, the capsules and the dispersal mechanism of Phialiphora. The description of these two new species exemplifies the uniqueness of the dry vegetations on unconsolidated white sands in western Madagascar, which are characterized by a high level of endemicity.